Acacia auriculiformis - A natural dye used for simultaneous coloration and functional finishing on textiles. (1st February 2020) - Chakraborty, Lina; Pandit, Pintu; Roy Maulik, Sankar
Abstract: Acacia auriculiformis can be effectively used for simultaneous dyeing and finishing of protein and cellulosic textile substrates. Wool and silk fabrics dyed with Acacia auriculiformis exhibit excellent colourfastness to washing and good light fastness properties. The phytochemical studies indicate the presence of saponin, phenols, tannin and glycosides in the aqueous extract of the colourant. Cotton, eri and wool fabrics dyed with aqueous extract of Acacia auriculiformis (200 g/l) results in maximum UPF value. Dyed fabrics are having excellent resistance against S. aureus and E. coli . There is an improvement in surface colour strength (measured in terms of K/S values) for all the dyed fabrics with the increase in dye concentration. The positive values of a* and b* indicates that the colour of the dyed fabrics is in red-yellow quadrant.